Miniaturised Triangular Microstrip Antenna with Metamaterial for Wireless Sensor Node Applications. Issue 2 (4th March 2022) - Mohan, C.; Florence, S. Esther
Abstract : This paper presents a simple, low cost and compact triangular microstrip antenna with metamaterial, designed for wireless sensor node applications. The proposed microstrip antenna consists of a triangular patch and circular shaped split ring resonator (SRR) as a ground plane. The metamaterial-based triangular microstrip patch antenna is designed at 2.4 GHz with a return loss of S11  < 10 dB and acceptable gain. The proposed antenna is of small size (0.065 λ0  × 0.065 λ0 ) and uses a FR-4 substrate of dielectric constant 4.3. The simulated and measured normalised radiation patterns are in concurrence with each other. The antenna covers 2.4 GHz ISM band making it appropriate for WSN applications.